Internal Fixation Construct and Defect Size Affect Healing of a Translational Porcine Diaphyseal Tibial Segmental Bone Defect. Issue 11 (26th November 2020) - McKinley, Todd O; Natoli, Roman M; Fischer, James P; Rytlewski, Jeffrey D; Scofield, David C; Usmani, Rashad; Kuzma, Alexander; Griffin, Kaitlyn S; Jewell, Emily; Childress, Paul; Shively, Karl D; Chu, Tien-Min Gabriel; et al.
ABSTRACT: Background and Objective: Porcine translational models have become the gold-standard translational tool to study the effects of major injury and hemorrhagic shock because of their similarity to the human immunologic response to trauma. Segmental bone defects (SBDs) typically occur in warfighters with associated severe limb trauma. The purpose of this study was to develop a translational porcine diaphyseal SBD model in Yucatan minipigs (YMPs), which could be used in bone healing investigations that simulate injury-relevant conditions. We were specifically working toward developing a critical sized defect (CSD). Methods: We used an adaptive experimental design in which both 25.0 mm and 40.0 mm SBDs were created in the tibial mid-diaphysis in skeletally mature YMPs. Initially, eight YMPs were subjected to a 25.0 mm SBD and treated with intramedullary nailing (intramedullary nail [IMN] 25mm). Due to unanticipated wound problems, we subsequently treated four specimens with identical 25.0 mm defect with dual plating (open reduction with internal fixation [ORIF] 25mm). Finally, a third group of four YMPs with 40.0 mm defects were treated with dual plating (ORIF 40mm). Monthly radiographs were made until sacrifice. Modified Radiographic Union Score for Tibia fractures (mRUST) measurements were made by three trauma-trained orthopedic surgeons. CT scans of the tibias were used to verify the union results. Results: At 4 months post-surgery, mean mRUST scores were 11.7 (SD ± 1.8) in the ORIF 25mm YMPs vs. 8.5 (SD ± 1.4) in the IMN 25mm YMPs ( P < .0001). All four ORIF 25mm YMPs were clinically healed. In contrast, none of the IMN 25mm YMPs were clinically healed and seven of eight IMN 25mm YMPs developed delayed wound breakdown. All four of the ORIF 40mm YMPs had flail nonunions with complete hardware failure by 3 months after surgery and were sacrificed early. CT scanning confirmed that none of the IMN 25mm YMPs, none of the ORIF 40mm YMPs, and two of four ORIF 25mm YMPs were healed. A third ORIF 25mm specimen was nearly healed on CT scanning. Inter-rater and intra-rater reliability interclass coefficients using the mRUST scale were 0.81 and 0.80, respectively. Conclusions: YMPs that had a 40 mm segment of bone removed from their tibia and were treated with dual plating did not heal and could be used to investigate interventions that accelerate bone healing. In contrast, a 25 mm SBD treated with dual plating demonstrated delayed but successful healing, indicating it can potentially be used to investigate bone healing adjuncts or conversely how concomitant injuries may impair bone healing. Pigs treated with IMN failed to heal and developed consistent delayed wound breakdown presumably secondary to chronic limb instability. The porcine YMP SBD model has the potential to be an effective translational tool to investigate bone healing under physiologically relevant injury conditions.